2007
DOI: 10.1007/s00244-006-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Liver Histopathologic Alterations in the Frog Rana ridibunda from a Small River of Northern Greece

Abstract: The various histopathologic alterations detected in the liver of the frog Rana ridibunda from a small river of Northern Greece were investigated. In the livers of the frogs collected from this river, there was an increase in the area occupied by melanomacrophages as well as an increase in their color intensity. Mild karyomegaly and polyploidy, together with solitary and focal accumulation of infiltrates (neutrophils and lymphocytes), was evident. Three different kinds of foci were detected basophilic focus, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…A similar increase has been reported in amphibians under both physiological or pathological conditions, such as exposure to low temperatures, oxygen deficit, infectious diseases, starvation, and exposure to heavy metals and other contaminants (Wolke, 1992;Barni et al, 1999;Frangioni et al, 2000;Loumbourdis and Vogiatzis, 2002;Fenoglio et al, 2005;Silva et al, 2013). In amphibians and other vertebrates, the melanin of the liver pigment cells seems to play an important role as scavengers of cytotoxic substances such as reactive oxygen species (ROS) or other toxic substances (Bustamante et al, 1993;Rozanowska et al, 1999;Loumbourdis, 2007). In particular, it has been hypothesized that in amphibians melanin may represent a valid alternative to enzymes involved in the detoxification, replacing the antioxidant activity of both superoxide dismutase (SOD) and glutathione (GSH) (Sichel et al, 1987;Geremia et al, 1989).…”
Section: Discussionmentioning
confidence: 70%
“…A similar increase has been reported in amphibians under both physiological or pathological conditions, such as exposure to low temperatures, oxygen deficit, infectious diseases, starvation, and exposure to heavy metals and other contaminants (Wolke, 1992;Barni et al, 1999;Frangioni et al, 2000;Loumbourdis and Vogiatzis, 2002;Fenoglio et al, 2005;Silva et al, 2013). In amphibians and other vertebrates, the melanin of the liver pigment cells seems to play an important role as scavengers of cytotoxic substances such as reactive oxygen species (ROS) or other toxic substances (Bustamante et al, 1993;Rozanowska et al, 1999;Loumbourdis, 2007). In particular, it has been hypothesized that in amphibians melanin may represent a valid alternative to enzymes involved in the detoxification, replacing the antioxidant activity of both superoxide dismutase (SOD) and glutathione (GSH) (Sichel et al, 1987;Geremia et al, 1989).…”
Section: Discussionmentioning
confidence: 70%
“…Other studies have shown phagocytic activity of melanomacrophages in the liver of amphibians living in polluted areas (Fenoglio et al. ; Loumbourdis ), and evidenced hemocatheresis by staining precipitated hemosiderin with Perls stain (Fenoglio et al. ).…”
Section: Discussionmentioning
confidence: 96%
“…; Fenoglio et al. ; Loumbourdis ). The ultrastructural study also demonstrated this parallel, showing a melanomacrophage and its membrane extensions engulfing two cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations